(untitled) (Revista Direitos Humanos e Democracia, 2021)
The purpose of the article is to reflect on the use of conflict mediation for the treatment of school conflicts and on the importance of an education through mediation, considering its pedagogical potential, and for mediation, as a condition for the effectiveness of Brazilian National Policy for Appropriate Treatment of Conflicts of Interests. It contains a bibliographic review and the report of empirical experiences.